The Effectiveness of Pharmacological Agents for the Treatment of Uveitic Macular Edema (UMO): A Systematic Review. (19th May 2019) - Tallouzi, Mohammad O.; Moore, David J.; Barry, Robert J.; Calvert, Melanie; Mathers, Jonathan; Murray, Philip I.; Denniston, Alastair K.
ABSTRACT: Purpose : To conduct a systematic review of effectiveness of pharmacological therapies for treatment of Uveitic Macular Edema (UMO). Method/Design : Comparative studies of pharmacological therapies in patients with UMO were identified in Cochrane CENTRAL/MEDLINE/EMBASE/CINAHL/trials registers (February 2017). PROSPERO registration: CRD42015019170. Results : Thirty-one studies were included. Corticosteroids were the most frequently studied ( n = 20). Corticosteroids (all forms) were consistently of greater/equal efficacy to active comparators; for anti-VEGF ( n = 4) improvement, best-corrected visual acuity (BCVA) and central macular thickness (CMT) were mostly less than local corticosteroid injection; for interferon ( n = 1) improvement BCVA and CMT were greater than the comparator of methotrexate; for topical indomethacin ( n = 1) improvement, BCVA and CMT were greater than placebo. Non-steroidal anti-inflammatory drugs, carbonic anhydrase inhibitors, and vitamin E ( n = 5) were not effective for these outcomes. Conclusion : The review highlights areas where the evidence base is still lacking, and appropriately focused trials are needed to inform best treatment to tackle this sight-threatening condition.